The legal consequences of the August 2008 Russian-Georgian military conflict: how does the "creeping occupation" carried out by Russia violate Georgia's sovereignty and the Georgian people’s rights? - Tchabashvili, Zurabi (Riga Graduate School of Law, 2017)
The present thesis illustrates how the "creeping occupation" violates Georgia’s territorial integrity and fundamental human rights based on the historical, as well as the 2008 and subsequent developments. Stemming from the current political events, the number of IDPs is a big problem across the world. All this is stipulated by very common international or non-international conflicts that are happening in today's world. These conflicts also include the problems of people internally displaced from the occupied territories in Georgia.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Russian-Georgian military conflict; Human rights